Aspergillus Flavus reprogrammed morphological and chemical attributes of Solanum lycopersicum through SlGSH1 and SlPCS1 genes modulation under heavy metal stress. Issue 1 (1st January 2021) - Aziz, Laila; Hamayun, Muhammad; Rauf, Mamoona; Iqbal, Amjad; Husssin, Anwar; Khan, Sumera Afzal; Irshad, Muhammad; Lee, In-jung
ABSTRACT: Cadmium (Cd) and chromium (Cr) in agricultural soils is becoming a serious threat in tomato. The complete removal of these heavy metals (HMs) from contaminated soil is challenging. However, the use of plant endophytes might be beneficial. The pragmatic role of endophytic fungi Aspergillus flavus (Ch-01) in tomato under Cd and Cr stress was, therefore, investigated. A. flavus enhanced growth attributes in tomato seedlings under Cd and Cr stress. Besides, it remediated Cd and Cr toxicity by reducing their translocation from the roots to the upper part of the tomato plants. In fact, A. flavus associated plants developed tolerance against Cd and Cr toxicity via the expression of SlGSH1 and SlPCS1 genes. Both genes helped in metal chelation and mitigation of Cd and Cr toxicity. From the results, it is concluded that A. flavus is a plant growth promoting and HMs alleviating endophyte, hence it might be used as a biofertilizer.